rozwiaz rownanie (2×-5)^2=(5×-2)^2
może ktoś pomoże?​



Odpowiedź :

Maris3

Odpowiedź:

do tego równania trzeba zastosować wzór skróconego mnożenia

[tex](a - b) ^{2} = {a}^{2} - 2ab + {b}^{2} [/tex]

[tex](2x - 5)^{2} = (5x - 2) ^{2} \\ (2x)^{2} - 5 \times 2x \times 2 + {5}^{2} = (5x) ^{2} - 5x \times 2 \times 2 + {2}^{2} \\ 4 {x}^{2} - 20x + 25 = 25 {x}^{2} - 20x + 4 \: \: \: \: \: | + 20x \\ 4 {x}^{2} + 25 = 25 {x}^{2} + 4 \\ 25x^{2}-4x^{2}=25-4\\21x^{2}=21 \: \: \: \: \: | \div 21 \\ x^{2}=1 \: \: \: \: \: |\sqrt{} [/tex]

x=1 v x=-1